HUBUNGAN UMUR DAN PARITAS IBU HAMIL TRIMESTER I DENGAN ANGKA KEJADIAN HIPEREMESIS GRAVIDARUM DI RSUD dr. MURJANI SAMPIT TAHUN 2017 - puspita sari pribadi (Jurnal Ilmiah Kebidanan dan Kesehatan Wanita, 2018)
Background : Hyperemesis gravidarum is nausea vomiting that to pregnant women thus disturbing the everyday work and is generally a bad, because there is dehydration. In the year 2011 there were the pregnancy in the world to reach 515.000 the soul and the hyperemesis gravidarum about (15 % - 20 %) of the 2012 estimates that at least 790.000 of pregnant women who experience hyperemesis gravidarum about (10%-14 %) of the number of pregnant women. Based on the preliminary study in the dr. Murjani Sampit New 2017 there are 55 people pregnant women trimester with hyperemesis gravidarum. Objective : The aim of study was to analyze the relationship Age and Paritas Mother Pregnant Trimester I with The Genesis Hiperemesis Gravidarum in the dr. Murjani sampit year 2017. Methods : This study using the method of analytic with the design of the case control. The entrie research population samples of 74 people who use the techniques of random sampling of data from secondary. Variables are free to age and of parity and variables tied the hyperemesis gravidarum. The result : The result this research thre are 74 responders with the age of 20 tahun-35 a 39 year of respondents (52,7 %). Meanwhile from 74 of the respondents of parity multipara a total of 40 respondents (54, 5), while the frequency of events hyperemesis gravidarum to as many as 37 of the respondents (50 %), and frequency doesn't happen hyperemesis gravidarum to as many as 37 of the respondents (50 %). Keywords : Age, Parity, Genesis of Hyperemesis Gravidarum.